The Impact of Perfluoroalkyl Substances on the Clinical Manifestations of Primary Sjögren Syndrome - Yun Zhao; Hangbiao Jin; Shetuan Hu; Songzhao Zhang; Meirong Zhao; Jing Xue (Toxics)
Sjogren’s syndrome is an autoimmune disease that may be triggered by environmental factors. While the impact of perfluoroalkyl substances (PFASs) on the human immune system has been investigated, their specific effect on Sjogren’s syndrome remains unreported. We conducted this study to evaluate the association between PFAS exposure and clinical manifestations of pSS. In total, 136 patients with pSS and 148 healthy controls in the Second Affiliated Hospital of Zhejiang University School of Medicine were investigated. The concentrations of perfluoroundecanoic acid (PFUdA) in the pSS group were statistically significantly higher than those in the healthy control group. Compared to patients without leukopenia and thrombocytopenia, those with the condition had significantly lower concentrations of perfluorononanoic acid (PFNA). The serum levels of PFNA and perfluorodecanoic acid (PFDA) were found to be lower in patients with a high antinuclear antibody (ANA) titer compared to those with a low ANA titer. The serum levels of PFNA were found to be lower in patients who were anti-Sjögren’s syndrome A (anti-SSA)-positive compared to those who were anti-SSA-negative. These results indicate that the levels of serum PFASs may be correlated with the disease activity in pSS patients, and there might be an association between PFASs and the onset of pSS.